Communication Behavior of Seller Community: An ethnographic study of communication of sellers to prospective buyers in the Manonda market, Palu - Jamiluddin, Jamiluddin; Yodo, Sutarman; Nur Ali, Muhammad; Badji, Haslinda; Yani, Ahmad (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: This phenomenon becomes more evident because traders who sell in the Manonda Market in Palu, consist of several different ethnic groups. The study aimed to describe and elaborate the communication behavior of sellers to prospective buyers, analyze variations in speech acts and meanings caused by variations in speech acts expressed by sellers to prospective buyers. A number of nine informants were involved in this study consisting of types of vegetable sellers, cloth sellers, clothing, fish sellers, and fruit sellers, where the three ethnic sellers, (Bugis, Kaili, and Javanese ethnicity) respectively represented by three sellers. The results of the study showed that the communication behavior of Bugis and Kaili ethnic sellers to prospective buyers generally used verbal and nonverbal communication behaviors in buying and selling interactions. Verbal communication is often presented in the form of perlocutionary acts, intended to influence prospective buyers or to influence the speech partner. Both of these ethnicities use an accommodative and persuasive communication model. While Javanese ethnic sellers, variations in speech acts contain more connotative meanings, which are poetic and metaphorical. Acted speech acts are a form of meaning that sounds polite, not too sharp, but the purpose is to disguise the true meaning. Javanese ethics in communication behavior more often expect high level culture through perlocutionary act.